PENENTUAN LINTASAN OPTIMAL DISTRIBUSI BARANG MENGGUNAKAN HYPERGRAPH - PARTITIONING DAN ALGORITMA GENETIKA - Sadiyyah, Fitriani Halimatus; Yulianti, Kartika; Sispiyati, Ririn (Universitas Jenderal Soedirman, 2024)
Efficient distribution of goods is critical in logistics management, which requires the selection of optimal distribution paths to achieve delivery targets with minimal total distance. This research combines Hypergraph-Partitioning and genetic algorithm to determine the optimal distribution path of goods to several customers. The Hypergraph-Partitioning divides the goods to be distributed equally to several vehicles, while the genetic algorithm is applied to determine the best distribution path in each partition. The results showed that the Hypergraph-Partitioning method successfully divided 62 customers into two partitions. The first partition serves 31 customers with a total demand of 865 loaves of bread, while the second partition also serves 31 customers with a total demand of 1,035 loaves of bread. The genetic algorithm was then used to find the shortest path for each partition, resulting in an efficient distribution solution.